Determinan Derajat Desentralisasi Fiskal Dan Pertumbuhan Ekonomi Kabupaten/Kota Di Provinsi Bali - Insan Putri, Tristia Izzatunnisa Azzahra; Mahaendra Yasa, I Nyoman (Innovative: Journal Of Social Science Research, 2024)
This study aims to identify the factors that affect the degree of fiscal decentralization and economic growth in various regions in Bali Province. Secondary data were collected through non-behavioral observation methods and in-depth interviews, then analyzed using path analysis. The results of the study revealed that the occupancy rate of hotels and private investment had a positive and significant impact on the degree of fiscal decentralization in the districts/cities of Bali Province, while the balance fund did not show any influence on this degree. Hotel occupancy rates have a positive and significant influence on economic growth in districts/cities in Bali Province, while private investment and the degree of fiscal decentralization have no effect. On the other hand, the balance fund does not have a positive and significant effect on economic growth in Bali Province. Hotel occupancy rates, private investment, and balance funds do not affect economic growth indirectly through the degree of fiscal decentralization in the Bali Province area. To overcome development disparities, the government needs to increase Regional Original Revenue (PAD) in each district/city by focusing on the development of certain sectors to reduce dependence on balance funds.